Public Housing Project Delivery in Nigeria: Quality versus Quantity - Oluwafemi Kehinde AKANDE; Lilian Chioma OBI-GEORGE; Jonam Jacob LEMBI; Ibrahim Adamu UMAR; Amos Musa TARNI; Adanna Joy NWOKORIE; Paul Haruna BABA (Alanya Üniversitesi, 2024)
The outbreak of COVID-19 and its consequences have altered people's perceptions of the availability of high-quality housing. Nigeria, the most populous country in sub-Saharan Africa, has taken many initiatives to address its growing population's housing demands. However, considerable focus has been placed only on housing quantity at the expense of housing quality. This study aims to investigate the interplay of factors affecting the provision of high-quality public housing projects in Nigeria. The objective is to identify the factors that significantly influence project success and failure in the delivery of quality public housing projects. A descriptive survey design with 351 randomly selected households and built environment experts (BEPs) was used. A self-developed structured questionnaire was used to collect data from households, buildings, and professionals over the course of three months. The findings indicate that in several buildings, the indoor air temperature and relative humidity extend acceptable limits (for example, 28 °C and 70% RH), which can have an effect on indoor air quality. Meanwhile, responses from the BEPs revealed that in order to develop high-quality housing, adequate project financing, evaluation of suitable building materials, and project management expertise were required. The study's conclusion emphasises that considering only the number of houses required to accommodate Nigeria's growing urban population is insufficient; rather, other factors such as appropriate design for improved air quality, high-quality and appropriate building materials, adequate project financing, and project management expertise would result in the quality delivery of livable public housing in Nigeria.